M MEMBENTUK KARAKTER RELIGIUS SISWA MELALUI PRAKTIK PENDIDIKAN ISLAM MODERAT DI SMP PSM TANEN REJOTANGAN TULUNGAGUNG - Sholikhah, Maratus; Khilwa, Amalia Rizki Lailatul; Azizah, Farida Nur; Amelia, Fatma; Junaris, Imam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the forms of moderate Islamic education practices and their implications for the formation of students' religious character at SMP PSM Tanen Rejotangan Tulungagung. The study used a descriptive qualitative approach with observation, interview, and documentation techniques. The results showed that moderate Islamic education practices are implemented through habituation of worship such as congregational Dhuha and Dhuhur prayers, Friday Legi recitation, teacher role models, and life-story-based learning to instill the values ​​of tolerance and non-judgmental attitudes towards differences. Supporting factors for religious character formation include a religious school culture, teacher support, and a conducive social environment, while the main obstacles come from students' low understanding of the concept of moderation and the influence of digital technology. The implications of implementing moderate Islamic education are seen in increased religious discipline, growing attitudes of tolerance, the formation of positive social behavior, and strengthening students' religious identity. Thus, moderate Islamic education has proven to be an effective approach in forming a religious character that is inclusive, balanced, and adaptive to diversity.